INVESTIGATING THE IMPACT OF ARTIFICIAL INTELLIGENCE ON HUMAN RESOURCE FUNCTIONS IN THE BANKING SECTOR OF PAKISTAN: A MEDIATED MODERATION MODEL - SH.M. Fakhr-e-Alam Siddiqui; Hammad Zafar; Zehra Zaidi (Policy Research Journal, 2025)
This study explores the influence of artificial intelligence (AI) on human resource (HR) functions within Pakistan's banking sector using a mediated moderation model. The research focuses on how AI technologies influence HR activities, strategic decision-making, and operational efficiencies. Methodologically, the study adopts a quantitative research approach, utilizing a structured questionnaire to gather data from HR professionals in different banks throughout Pakistan. A sample size of 200 respondents was targeted, with a response rate of 80%. The collected data was analyses using structural equation modelling to understand the relationships between variables. The results indicate that AI significantly enhances HR functions, particularly in recruitment, performance management, and employee engagement. Additionally, the study identifies a mediating effect of organizational readiness and a moderating effect of ethical considerations on the relationship between AI implementation and HR outcomes. The findings suggest that while AI offers substantial benefits, its success is contingent on ethical practices and organizational preparedness. These insights have implications for HR professionals and policymakers in the banking sector, highlighting the need for comprehensive strategies to integrate AI while addressing ethical and readiness concerns.